Bidirectional crosstalk between periventricular endothelial cells and neural progenitor cells promotes the formation of a neurovascular unit - Vissapragada, Ravi; Contreras, Mauricio A.; da Silva, Cleide G; Kumar, Vivek A.; Ochoa, Angelica; Vasudevan, Anju; Selim, Magdy H.; Ferran, Christiane; Thomas, Ajith J. (Brain research, 2014)
Interactions between neural progenitor cells (NPC) and endothelial cells (EC) from adult vascular beds have been well explored previously. However, the factors and signaling mechanisms that regulate neurogenesis and angiogenesis are most prevalent during embryonic development. This study aimed to determine whether embryonic brain endothelial cells from the periventricular region (PVEC) present an advantage over adult brain EC in supporting NPC growth and differentiation. PVEC were isolated from E15 mouse brains, processed, and sorted with immunomagnetic beads using antibodies against CD31/PECAM. On immunofluorescence (IF) staining, nearly all cells were positive for EC markers CD31 and CD144/VE-Cadherin. In proliferation studies, NPC proliferation was highest in transwell co-culture with PVEC, approximately 2.3 fold increase compared to baseline versus 1.4 fold increase when co-cultured with adult brain endothelial cells (ABEC). These results correlated with the PVEC mediated delay in NPC differentiation, evidenced by high expression of progenitor marker Nestin evaluated by IF staining. Upon further characterization of PVEC in an angiogenesis assay measuring cord length, PVEC exhibited a high capacity to form cords in basal conditions compared to ABEC. This was enhanced in the presence of NPC, with both cell types displaying a preferential structural alignment resembling neurovascular networks. PVEC also expressed high Vegfa levels at baseline in comparison to NPC and ABEC. Vegfa levels increased when co-cultured with NPC. We demonstrate that PVEC and NPC co-cultures act synergistically to promote the formation of a neurovascular unit through dynamic and reciprocal communication. Our results suggest that PVEC/NPC could provide promising neuro-regenerative therapies for patients suffering brain injuries. •Interactions between neural progenitor cells (NPC) and periventricular endothelial cells (PVEC) were delineated.•Embryonic brain endothelial cells (PVEC) present an advantage over adult brain EC in supporting NPC growth and differentiation.•PVEC enhanced NPC proliferation and delayed NPC differentiation as evidenced by high expression of progenitor marker Nestin.•PVEC expressed increased Vegfa levels when co-cultured with NPC.•PVEC/NPC could provide promising neuro-regenerative therapies for patients suffering brain injuries.